A Community of Practice for Gender-Transformative Research Methodologies - Rietveld, Anne M.; Gartaula, Hom Nath; Farnworth, Cathy Rozel; López, Diana E.; Bailey, Arwen; Hellin, Jonathan; Fisher, Eleanor; Kramer, Berber; Teeken, Béla; Mujawamariya, Gaudiose; Choudhury, Afrina (CGIAR GENDER Impact Platform, 2022)
The Community of Practice on Gender-Transformative Research Methodologies (GTRM-CoP) builds on work conducted by international gender researchers at CGIAR and partner organizations. The community of practice is committed to gender-transformative change processes; and aims to co-create socially just and gender-equitable futures in food, land and water systems. The GTRM-CoP aims to promote the transformative ambitions of CGIAR, its partners, and interested organizations and individuals, by creating safe spaces for innovating, sharing and scaling gender-transformative research methodologies. The community of practice is part of the CGIAR GENDER Impact Platform and housed under the Methods module of the Platform. A Community of Practice (CoP) is an ideal mechanism for promoting rapid, interactive and creative learning. Four initial topic groups have been identified to begin knowledge exchange and co-creation: gender-equitable masculinities, intersectionality, transformative research processes and data, and mobilizing GENNOVATE data and tools. The GTRM-CoP aims to accelerate learning and action that fosters gender-transformative change in food, land and water systems, through the interactions within and between the topic groups, following a set of principles and values and in a spirit of humility and learning. These lessons will be available to others within CGIAR and beyond as part of a global movement toward gender equity and achieving Gender Equality (SDG 5) and Reduced Inequalities (SDG 10).